Minimally‐invasive plate osteosynthesis of a Salter‐Harris type 2 fracture of the proximal phalanx in a filly. (3rd February 2015) - Van Spijk, J. N.; Fürst, A. E.; Del Chicca, F.; Ringer, S. K.; Jackson, M. A.
Summary A 7‐month‐old Warmblood filly was referred to the equine hospital because of a Salter‐Harris type 2 fracture of the proximal physis of the right hind P1. On admission, the filly had acute grade 3/5 lameness at the walk and diffuse swelling in the area of the right hind proximal phalanx. Radiographs were taken to assess the fracture and plan treatment. Surgical treatment using two 4.5 mm narrow locking compression plates (PIP‐LCPs) resulted in fracture stabilisation and rapid healing. This case report suggests that internal fixation using PIP‐LCPs is useful for the treatment of Salter‐Harris type 2 fractures of the proximal physis of P1 in large foals.